Lithium Battery Efficiency Analysis in Solar Power Plants (PLTS) for Rice Field Irrigation Water Pumps - Prabowo, Deni; Muhammad Erpandi Dalimunthe; Zuraidah Tharo (Sean Institute, 2025)
Solar Power Plant is a power generation system that uses solar energy to generate electricity. PLTS components consist of solar panels, solar charger controller, battery and inverter. Solar panels are used to convert solar energy into DC electrical energy. The solar charger controller functions to regulate the voltage value distributed to the battery. The battery is used to store electrical power and the inverter is used to convert DC current to AC. In its use, the components installed on the PLTS need to know the efficiency percentage so that the amount of electrical energy utilization that can be generated can be known. This study aims to analyze the efficiency of electrical energy generation produced by solar panels with a capacity of 250 WP and a 2000 W inverter. Tests were carried out 5 times within a 5-hour time span (10:00 WIB – 14:00 WIB) using a 350 W Water Pump load. The test results showed that the solar panels were able to produce an average power of 76.39 W, with the largest power reaching 86.55 W. The calculated solar panel efficiency was 15.13%. The battery efficiency, based on the highest power measured, reached 0.80%. The inverter's power output varied, averaging 919.6 watts, with the highest output reaching 935 watts.